Synthesis of terminal communication of the combined bridge synchronization under astatism order increase - Козловський, Валерій Валерійович; Туровський, О. Л.; Баланюк, Ю. В. (Science-based technologies, 2020)
The purpose of the article is theoretical research in the direction of development, analysis and improvement of known and synthesis of new synchronization schemes, characterized by high noise immunity, accuracy and speed with simplicity of design. The problem to be solved is to investigate closed and combined synchronization systems, to obtain analytical ratios and on their basis to develop a methodology that allows: to determine the type and parameters of open communication in the combined synchronization system; increase the order of astatism of the specified system; to reduce the variance of the constant and transient errors in the process of carrier frequency tracking in the presence of noise in the communication channel. The following results were obtained. Closed-loop synchronization systems are analyzed, their discrepancies are determined for increasing the order of astatism and minimizing the variance of phase error during carrier frequency monitoring. A model for a combined disconnect synchronization system is proposed. The problem of synthesis of open communication in the combined system of synchronization is solved with the condition of increasing the order of astatism, while monitoring the carrier frequency (pilot - signal), the phase of which is modulated by a deterministic Doppler signal. Analytical ratios and on their basis are offered a method that allows to determine the type and parameters of open communication in a combined system of synchronization, provided that the order of astatism of the system is increased to the required value. Conclusions. Considering the additive Gaussian noise and the instability of the generators, the desire to minimize the variance of the phase error in the class of closed systems of synchronization causes a deterioration of the system dynamics and does not allow to increase the order of astatism. Introduction to the open channel of the combined system of synchronization of physically realized units, allows to increase the order of astatism of the system and to synthesize invariant systems. The use of the frequency discriminator as an open link allows to increase the order of astatism of the combined system of synchronization of the system to the second order. The open channel is made in the form of parallel (sequential) inclusion of two links of the frequency discriminator with the proposed transfer function allows to increase the order of astatism to the third and higher order and does not affect the stability of the system